Prospective, observational study of opioid usage after hip arthroscopy for femoroacetabular impingement syndrome: Opioid usage after hip arthroscopy - Cunningham, Daniel (Arthroscopy, 2018)
PURPOSE: The purpose of this study was to provide estimates of post-operative opioid usage after hip arthroscopy for femoroacetabular impingement syndrome and to identify risk factors for increased post-operative opioid usage. METHODS: All patients who were at least eighteen years old undergoing hip arthroscopy for femoroacetabular impingement syndrome with one of two hip preservation surgeons between November 2015 and August 2016 were eligible for inclusion in this study. Target minimum enrollment was set at 30 patients per surgeon based on an a priori sample size calculation. Enrolled patients completed the International Hip Outcome Tool, visual analog pain scale, Pain Catastrophizing Scale, abbreviated Patient Health Questionnaire, and questions regarding demographics and opioid and anti-inflammatory usage. Opioid consumption was assessed through pill counting at 2-week and 6-week post-operative appointments. Of 80 patients enrolled, 67 patients had complete 2-week and 6-week opioid usage data. Patient and operative factors were correlated with outcomes in multivariable models. RESULTS: Opioid usage in the 2 weeks prior to surgery was significantly associated with higher post-operative opioid usage at 2-weeks (253.8 additional OME’s, 95% CI 171.2–336.5, p<0.0001, n=73) and 6-weeks (385.3 additional OME’s, 95% CI 241.6–529.0, p<0.0001, n=67) post-operative. By 6-weeks post-operative, 41/52 (79%) of patients without opioid usage in the 2 weeks prior to surgery used 30 or fewer oxycodone 5-mg pills compared to only 2/15 (13%) of patients with pre-operative use (24.9 odds ratio, 95% CI 4.2–148.5, p<0.0001). CONCLUSION: Among patients undergoing hip arthroscopy for femoroacetabular impingement syndrome, any opioid usage in the two weeks preceding surgery was the strongest predictor of opioid usage after hip arthroscopy. The impact of pre-operative opioid usage far exceeded the impact of other baseline patient and operative factors. Assessment of pre-operative opioid usage could be an important factor in guiding post-operative opioid prescribing. LEVEL OF EVIDENCE: II, prospective observational study